Curriculum Reform in Ontario 'Common-Sense' Policy Processes and Democratic Possibilities - Pinto, Laura Elizabeth (University of Toronto Press, 2018)
This first full account of curriculum policy formulation in 1990s Ontario helps readers understand the real-life experiences of policymakers both within the province and internationally.Having worked as a policy analyst for the Government of Ontario, a public school teacher, and a university professor, author Laura Elizabeth Pinto is uniquely positioned to tackle the key issues of policy formulation: the politics and tensions among different policy actors; the relationships between democracy in education and in policy formation; and the hidden role of privatization.Based on interviews with key policy actors, including ministry bureaucrats, curriculum policy writers, stakeholder consultation participants, and political staffers, Curriculum Reform in Ontario provides a critique of conventional policy formulation processes. Pinto also suggests possibilities for more participatory approaches to policy formulation that can better support the critical role played by schools in creating democratic societies